What happened to Rachel Riley? - Swinarski, Claire (Quill Tree Books, an imprint of HarperCollinsPublishers, 2023)
"Thirteen-year-old new girl Anna Hunt decides to make an investigative podcast about how fellow classmate Rachel Riley went from being the most popular girl in school to the most hated"--